(untitled) (Journal of the College of Basic Education, 2022)
The aim of the research is to find out the effect of two teaching strategies, brainstorming and (Think-Pair-Share) on the achievement and intelligence in mathematics of fourth-grade female students in mathematics. The research sample consisted of (75) students from a secondary school in Baghdad, divided into three groups that studied The first group was taught by the brainstorming strategy, and the second group was studied using the (Think - Pair - Share) strategy. The third group was taught in the traditional way. The researcher built two research tools (achievement test, intelligence test in mathematics),